Self-testing for HIV, HBV, and HCV using finger-stick whole-blood multiplex immunochromatographic rapid test: A pilot feasibility study in sub-Saharan Africa. - Serge Tonen-Wolyec; Roland Marini Djang'eing'a; Salomon Batina-Agasa; Charles Kayembe Tshilumba; Jérémie Muwonga Masidi; Marie-Pierre Hayette; Laurent Bélec (PLoS ONE)
Background The burden of HIV, HBV, and HCV infections remains disproportionately high in sub-Saharan Africa, with high rates of co-infections. Multiplex rapid diagnostic tests for HIV, HBV and HCV serological testing with high analytical performances may improve the "cascade of screening" and quite possibly the linkage-to-care with reduced cost. Based on our previous field experience of HIV self-testing, we herein aimed at evaluating the practicability and acceptability of a prototype finger-stick whole-blood Triplex HIV/HCV/HBsAg self-test as a simultaneous serological screening tool for HIV, HBV, and HCV in the Democratic Republic of the Congo (DRC). Methods A cross-sectional multicentric study consisting of face-to-face, paper-based, and semi-structured questionnaires with a home-based and facility-based recruitment of untrained adult volunteers at risk of HIV, HBV, and HCV infections recruited from the general public was conducted in 2020 in urban and rural areas in the DRC. The practicability of the Triplex self-test was assessed by 3 substudies on the observation of self-test manipulation including the understanding of the instructions for use (IFU), on the interpretation of Triplex self-test results and on its acceptability. Results A total of 251 volunteers (mean age, 28 years; range, 18-49; 154 males) were included, from urban [160 (63.7%)] and rural [91 (36.3%)] areas. Overall, 242 (96.4%) participants performed the Triplex self-test and succeeded in obtaining a valid test result with an overall usability index of 89.2%. The correct use of the Triplex self-test was higher in urban areas than rural areas (51.2% versus 16.5%; aOR: 6.9). The use of video IFU in addition to paper-based IFU increased the correct manipulation and interpretation of the Triplex self-test. A total of 197 (78.5%) participants correctly interpreted the Triplex self-test results, whereas 54 (21.5%) misinterpreted their results, mainly the positive test results harboring low-intensity band (30/251; 12.0%), and preferentially the HBsAg band (12/44; 27.3%). The rates of acceptability of reuse, distribution of the Triplex self-test to third parties (partner, friend, or family member), linkage to the health care facility for confirmation of results and treatment, and confidence in the self-test results were very high, especially among participants from urban areas. Conclusions This pilot study shows evidence for the first time in sub-Saharan Africa on good practicability and high acceptability of a prototype Triplex HIV/HCV/HBsAg self-test for simultaneous diagnosis of three highly prevalent chronic viral infections, providing the rational basis of using self-test harboring four bands of interest, i.e. the control, HIV, HCV, and HBsAg bands. The relatively frequent misinterpretation of the Triplex self-test points however the necessity to improve the delivery of this prototype Triplex self-test probably in a supervised setting. Finally, these observations lay the foundations for the potential large-scale use of the Triplex self-test in populations living in sub-Saharan Africa at high risk for HIV, HBV, and HCV infections.